(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article analyzes the content and methodological model of an integrated creative approach. The importance of a creative approach in improving the effectiveness of education through interdisciplinary connections, the development of creative thinking, and the use of modern technologies is shown. The issues of improving the skills of teachers and modernizing the educational process are also discussed.